PROBLEMS OF STRATEGIC MANAGEMENT OF BUSINESS PROCESSES IN THE CONTEXT OF INTEGRATED DIGITALIZATION OF HIGH-TECH INDUSTRIES - N. N. Trofimova (Вестник университета)
A study of the problematic issues of strategic management in Russian industry which arise during the digitalization of high-tech industries has been conducted. The research methodology was analytical in nature, with the author`s emphasis on the analysis of business process management of industrial enterprises in Russia at the current stage of transition to the digital economy. In practical terms, this will serve as the basis for creating effective tools for modernizing production processes and optimizing business processes in high-tech industries, based on the use of strategic analysis methods on management issues in the context of complex industrial digitalization. The novelty and scientific value of the work lies in the fact that the result of the study was a reasonable author’s approach to studying the specifics of the digital economy in Russian industry, as well as the development of an algorithm for identifying and solving existing problems of digitalization, taking into account the peculiarities of high-tech industries.